Effects of cooperative learning on student performance in mathematics. - Dalisay, Jesse Noita Bonilla
This study aimed to know if cooperative learning affects student performance in Mathematics. Peer tutotring and Students-Teams Achievement Division (STAD) are the two cooperative learning strategies included in this study. The participants of the study were students enrolled in Mathematics 11 in the Second Semester (SY 1997-1998). A pretest was conducted using a 15 item quiz on Operations on Rational Expressions. The matching variable for the experiment was the quiz scores of the participants on the pretest. The partcipants were assigned to four-member teams in the Student-Teams Achievement Division. A peer tutor (those who obtained a quiz score ranging from 0-5). Each team and pair were given worksheets on Rational Expressions that they studied for an hour as a team and/ or pair. After the team study, a 10-item exercise on Operations on Rational Expressions was given which they answered as a team. The effects of the cooperative learning strategies were measured through the participant's individual scores on the same 15-item quiz on the posttest. Two way Analysis of Variance and Tukey's test for post hoc comparisons were used in the statistical analysis of data. Results showed an increase in the score of the participants on the posttest. Participants assigned in peer tutoring teams and Student-Teams Achievement Division teams obtained much higher scores compared to their pretest scores. There was a significant difference between the mean quiz scores of the participants in the two cooperative learning strategies during the pretest and the posttest. Students who were assigned in peer tutoring teams performed better than those in STAD teams. In conclusion, cooperative learning affects student performance and peer tutoring, as a cooperative learning strategy is more effective compared to Student-Teams Achievement Division.